2017
DOI: 10.1186/s12957-017-1296-z
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and feasibility of total reconstruction versus nontotal reconstruction of the pelvic floor on short-term and long-term urinary continence rates after radical prostatectomy: a meta-analysis

Abstract: BackgroundRecently, total pelvic floor reconstruction (TR) has been the treatment of choice for improving urinary incontinence (UI) after radical prostatectomy (RP). However, the superiority of TR with respect to urinary continence recovery following RP remains controversial. This study identified the effect of TR versus nonTR of the pelvic floor on short-term and long-term continence rates after RP.MethodsA literature search was performed in November 2017 using the PubMed, Embase, and Web of Science databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The results of this study suggest that posterior reconstruction of the rhabdosphincter improves the early continence of patients undergoing LRP, as it is described in several studies (11,(22)(23)(24). Rocco et al (2007) conducted a prospective study on patients undergoing LRP, defining continence as no pads or one diaper/day.…”
Section: Discussionsupporting
confidence: 52%
“…The results of this study suggest that posterior reconstruction of the rhabdosphincter improves the early continence of patients undergoing LRP, as it is described in several studies (11,(22)(23)(24). Rocco et al (2007) conducted a prospective study on patients undergoing LRP, defining continence as no pads or one diaper/day.…”
Section: Discussionsupporting
confidence: 52%
“…According to these results, in a recent meta‐analysis that compared total vs non‐total reconstruction techniques for the recovery of continence, Wu et al. reported the superiority of total reconstruction techniques in terms of shorter time to recovery of continence after RP at every time point. Concerning early recovery of continence, the outcomes were statistically in favour of the total reconstruction techniques at 1 week (OR 2.76, 95% CI 1.58–4.84; P < 0.001), 2 weeks (OR 2.57, 95% CI 1.74–3.80; P < 0.001), 4 weeks (OR 2.61, 95% CI 1.56–4.38; P < 0.001), and 12 weeks (OR 4.33, 95% CI 2.01–9.33; P < 0.001) after RP.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al [43] demonstrated that anterior suspension (Patel's stitch) was also associated with short-term urinary continence, but not with long-term outcomes. Wu et al [44] performed a meta-analysis to evaluate the efficacy of total reconstruction (anterior plus posterior reconstruction) versus non-total reconstruction of the pelvic floor on the urinary continence rate after RP, with eight robotic and two laparoscopic RP series. There was a significant benefit on urinary incontinence at 52 weeks (OR, 4.10; 95% CI, 1.80-9.38; p < 0.001) in addition to short-term outcomes (1, 2, 4, 12, and 24 weeks); however, the continence outcome at longer than 52 weeks was not reported.…”
Section: Discussionmentioning
confidence: 99%